Pembangunan Jembatan Youtefa dan UMKM di Teluk Youtefa Distrik Muara Tami Kota Jayapura - Paula, Diana Yulia; Boari, Yoseb; Lestari , Endah Dwi; Kutumun, Weldemina (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2023)
Transportation is very important, because it is the lifeblood of economic, social, political, cultural and Defense and Security. Bridges as transportation infrastructure have dominant benefits for traffic drivers. Prior to the existence of the Youtefa Bridge as an alternative link between Jayapura - Muara Tami - Keerom, the condition of activities prior to the existence of the Youtefa Bridge, community activities and economic activities in Jayapura City only used one road, namely Jalan Nafri as the only main connecting route. The purpose of this study was to determine the impact of the Youtefa Bridge on MSMEs in the Teluk Youtefa Muara Tami District, Jayapura City. A qualitative descriptive research method with an inductive approach as well as observation, interviews, interviews and online data tracking in data collection techniques. The research results show that there are two impacts from the construction of the Youtefa Bridge, namely the positive impact and the negative impact. Positive impact, the establishment of new businesses such as; restaurants, cafes, shop houses, hotels, beach resorts, kiosks and stalls. Other positive impacts include building new offices, building BTN housing, renovating main roads and becoming a location for exercise. Meanwhile, the negative impact of the construction of the Youtefa Bridge was that the SMEs that were previously in Nafri, Kampung Pisang and Koya experienced a decrease in income, so some of them moved to a new business location, namely in Holtekamp Panjang. Another negative impact is that sometimes accidents often occur. At night there are no lights so it is prone to robbery